Formulasi dan Pengolahan Roti Isi Daging Ikan Tongkol (Euthynnus affinis) Sebagai Rintisan Produk Oleh-Oleh Khas - Nugroho, Teguh Setyo; Laksono, Untung Trimo; Masi, Aloysius (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
The development of the city of Pontianak has become a special attraction for residents and tourists to visit. This condition is certainly an opportunity for the development of various food/culinary businesses that can become souvenirs or souvenirs such as Tongkol Fish Meat (Euthynnus affinis) Stuffed Bread. The objectives of this research include: 1) to obtain the formulation and processing method for tuna fish meat sandwiches; 2) measure the level of panelists' liking (hedonic test) for taste, appearance, color, aroma and texture; 3) analysis of the costs and prices of tuna fish sandwiches. This research is a design experimental research using the kitchen project experimental method. The reference/reference for the recipe formulation and processing method for tuna fish meat sandwiches follows formulation A Umasugi (2020) and formulation B Endeus (2023). Based on the experimental results, the average level of preference for formulation B was 6.74 and was better than formulation A whose value was 6.58. The experimental results of formulation B which had been improved/modified showed better results, namely 7.51. Improvements/modifications to formula B are considered to have provided the expected results. The investment cost for producing cob-filled bread, assuming a production capacity of 160 boxes per day (per box containing 8 pieces of bread @ 35 grams), with a total of 2 employees, is Rp. 34,042,149,-. Production costs with a production capacity of 4,000 boxes per month (25 working days) are IDR 62,075,697, = which consists of fixed costs IDR. 7,596,097,- and variable costs Rp. 54,479,600,-. If the profit assumption is 10% of production costs, then the monthly profit is IDR 6,207,570.-..